Examining the Effects of Perceived Parental Attitudes on the Social Interest Level in College Students: The Mediating Role of Self-Esteem - Abdi Güngör; Merve Akyıldız (Sakarya University Journal of Education)
Social interest refers to the individual's sense of community and social benefit. Especially for university students, social interest is important in terms of their developmental period and their efforts to gain a place in society. Therefore, it would be helpful to investigate the factors potentially affecting the social interest levels of university students. This study aimed to investigate the effects of perceived parental attitudes and self-esteem on social interest levels in university students. In addition, this study aimed to examine the mediating roles of self-esteem on the relationship between parental attitudes and social interest. The participants included 438 volunteer university students. The data were collected using the Demographic Information Form, Social Interest Index, Parental Attitude Scale, and Rosenberg Self-Esteem Scale. The hypothesis model was tested using path analysis and bootstrapping method. The results showed that self-esteem partially mediated the effect of democratic attitude on social interest and fully mediated the effects of authoritarian attitude on social interest. The results also revealed that the protective attitude did not have a direct or indirect effect on social interest. The results were discussed along with the theoretical framework and previous findings, and suggestions for future research were presented.